2023
DOI: 10.2147/idr.s424345
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic review on Prevalence, Serotypes and Antibiotic resistance of Salmonella in Ethiopia, 2010–2022

Atsebaha Gebrekidan Kahsay,
Tsehaye Asmelash Dejene,
Enquebaher Kassaye

Abstract: Background In Ethiopia, salmonellosis is one of the most common zoonotic and foodborne illnesses. Ethiopia continues to be at risk for its fast-expanding medication resistance. For the development of preventative and control methods, summarized knowledge regarding salmonellosis is necessary. Determining a thorough evaluation of the prevalence, serotypes, and antibiotic resistance of Salmonella in humans and animals from January 1, 2010, to December 30, 2022, in Ethiopia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…In this study, we determined the prevalence and genetic diversity of Salmonella strains isolated from clinical and food samples collected in Jiaxing City, China. The detection rate of Salmonella among individuals with diarrhea was 3.98% (200/5019), which was consistent with previous findings obtained in Ethiopia and lower than that in Shanghai [34,35]. Several studies have demonstrated the dominant prevalence of monophasic S. Typhimurium in human, food, and environmental samples [36,37].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we determined the prevalence and genetic diversity of Salmonella strains isolated from clinical and food samples collected in Jiaxing City, China. The detection rate of Salmonella among individuals with diarrhea was 3.98% (200/5019), which was consistent with previous findings obtained in Ethiopia and lower than that in Shanghai [34,35]. Several studies have demonstrated the dominant prevalence of monophasic S. Typhimurium in human, food, and environmental samples [36,37].…”
Section: Discussionsupporting
confidence: 90%
“…S. Croft II and S. Jodhpur II were observed only in the environmental samples. In this review, we found that S. Typhi was highly prevalent in humans and was also reported in Ethiopia [ 81 ], China [ 82 ], the Middle East, and North Africa [ 58 ]. According to reports from sub-Saharan African nations, S. Typhimurium is one of the invasive forms of NTS, especially among susceptible people, such as those with HIV, malnourished children, and malaria [ 10 , 83 ].…”
Section: Discussionmentioning
confidence: 99%